The Reconstruction of Free Judgments in Corruption Crimes and Its Implications for Enforcement Laws in Indonesia - Ashal, Adam Sofyan; Sudiro, Amad (Dinasti Research, 2025)
Acquittals in corruption cases often generate controversy and undermine public trust, necessitating their reconstruction to strengthen justice and law enforcement in Indonesia and mitigate errors in the application of law (error in recht) in acquittal decisions. The problem at hand is how to reconstruct acquittals in corruption cases under the Corruption Eradication Law and the implications of acquittals for law enforcement in Indonesia. The research method used is normative juridical legal research. The results indicate that the reconstruction of acquittals in corruption cases is necessary to affirm justice and legal certainty. This effort requires limiting judicial interpretation, strengthening evidence, and tightening oversight to maintain judicial integrity and increase public trust. The reconstruction of acquittals strengthens accountability, transparency, and consistency in the judiciary, while ensuring substantive justice. This reform also increases public trust and strengthens commitment to corruption eradication and the rule of law.